Cosmopolitan Imagery: Prestigious Connections to the World in Contemporary Muslim and Christian Indonesian Pilgrimage Pictures - Lücking, Mirjam (International Journal of Islam in Asia, 2021)
Travel following religious aims has a long tradition in the Indonesian-Malay Archipelago. Yet mass overseas religious tourism is a relatively recent phenomenon among people in today’s Indonesia. A variety of travel agencies advertise pilgrimage package tours to notable destinations like Mecca and Medina but also to other destinations in the Middle East, Europe, East Asia, and Central Asia. An analytical focus on various images in this context, including their creation and distribution, reveals patterns of prestigious cosmopolitan middle-class imagery among Muslim and Christian Indonesians in the field of religious tourism. This imagery is similar across different religious affiliations and particularly vibrant in online social media. The imagery challenges perceptions of interreligious divisions and hegemonic mappings of the world, ultimately centralizing the local social environment of people and exhibiting national Indonesian pride.